Electrical Engineering Students’ Instrumental and Integrative Motivation in Learning English - Swari, Utami Ratna; Rahma, Ary Analisa; Arista, Hermin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Motivation compensates the success of foreign language learning. It is induced by two essential types: instrumental and integrative motivation. This research focuses on describing the students’ instrumental and integrative motivation in learning English. Twenty-eight students of Electrical Engineering Department of University of Panca Marga Probolinggo were involved in this research. The data about the students’ motivation were collected using questionnaire. The questionnaire was divided into two major parts which were used to find out two types of motivational orientation, following Gardner and Lamberts’s motivational measure. The data obtained from the students’ motivation opinionnaire was computer coded and processed with the Statistical Package for the Social Science (SPSS). The students were asked to indicate on a five-point scale to show how important each reason was for their learning English as a foreign language. From the data analysis, the overall mean score of instrumental motivation was 4.11, while integrative motivation was 3.68. The result showed that electrical engineering students in Panca Marga University were more motivated instrumentally in learning English.